RESPON KALUS KENCUR (Kaempferia galanga L.) TERHADAP CEKAMAN KEKERINGAN DENGAN PERLAKUAN POLYETHYLENE GLYCOL 6000 DAN NAPTHANELE ACETIC ACID - anis shofiyani shofiyani; Agus Mulyadi Purnawanto; Virza Carmelita (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2021)
Kencur (Kaempferia galanga L.) is a plant that has a high enough rhizome selling value. Increased production can be done by expanding the land. However, cultivated land in Indonesia is generally dominated by dry land with limited water availability. The research objective was to obtain galanga callus that were tolerant of drought in vitro using the PEG 6000 selective agent. Randomized block design (RBD) 2 factors were repeated 3 times. PEG 6000 concentrations were  0%, 5%, 10%, 15%, 20% and NAA concentrations were 1mg/l, 1.5mg/l, 2mg/l. The parameters observed were callus morphology (texture and color), wet weight, dry weight, percentage of fresh callus, number of roots, proline content, and live callus percentage. The results showed compact textures that were green, white, and brown. Wet weight, dry weight, percentage of fresh callus, number of roots of PEG 6000 treatment resulted in a decreasing value while the proline content increased with the increase in PEG 6000 concentration. The NAA treatment at the concentration of 1mg/l produced the most roots, while the percentage value of fresh callus was inversely proportional to the value of the proline content. The lower the PEG 6000 and NAA concentrations resulted in more roots. The higher the PEG 6000 concentration and the lower the NAA concentration resulted in high the proline content. PEG 6000 20% still produced 61% living callus.